Formulation design, development and characterization of dexibuprofen emulgel for topical delivery: In-vitro and In-vivo evaluation: IN-VITRO AND IN-VIVO EVALUATION - Mahajan, Vijay Rajaram; Basarkar, Ganesh Dinkar (Journal of Drug Delivery and Therapeutics, 2019)
Emulgels have emerged as a promising drug delivery system for the delivery of hydrophobic drugs. The objective of the study was to prepare emulgel of Dexibuprofen, a NSAID, using Carbapol 940 as a gelling agent. Clove oil and Mentha oil were used as penetration enhancers. The emulsion was prepared and it was added in gel base. The formulations were evaluated for rheological studies, spreading coefficient studies, bioadhesion strength, skin irritation studies, in vitro release, ex vivo release studies, anti-inflammatory activity and analgesic activity. Formulation showed comparable analgesic and anti-inflammatory activity when they compared with marketed diclofenac sodium gel. So, it can be concluded that topical emulgel of Dexibuprofen possess an effective anti-inflammatory and analgesic activity.Keywords: Emulgel, Dexibuprofen, Topical Drug Delivery, bioavailability, NSAIDs